Plasmon-Driven Selective Methane Oxidation to Formic Acid at Ambient Conditions - Nguyen, Thuy Ha; Park, Eun Duck; Yu, Sungju (ACS Energy Letters, 2024)
Harnessing the capabilities of plasmonic catalysts, we present a partial oxidation approach for the selective conversion of gaseous methane to liquid formic acid (HCOOH) while suppressing carbon dioxide production. This photoreaction capitalizes on the chemical potential inherent in charge carriers generated via the interband transitions of gold nanoparticles. These energetic electron and hole carriers interact profoundly with adsorbed oxygen molecules (O2), yielding reactive singlet oxygen (1O2) species. Our investigation shows spin-forbidden transitions facilitated by a dexter-type electron exchange process. Remarkably, the resultant 1O2 species effectively reduce the energy barrier associated with C−H bond activation to 24.8 ± 3.9 kJ mol−1. This process initiates the catalytic cascade following the Eley−Rideal model at ambient conditions. Consequently, it drives the preferential production of the oxygenated liquid product, HCOOH, demonstrating an impressive selectivity of >97%. This study offers a new perspective on the O2-mediated oxidation reaction that occurs on plasmonic catalysts.
Keywords: Ambient conditions; Gaseous methane; Gold nanoparticle; Gold Nanoparticles; Inter-band transition; Methane oxidation; Partial oxidations; Photoreactions; Plasmonics; ]+ catalyst